2014
DOI: 10.1177/1403494814561818
|View full text |Cite
|
Sign up to set email alerts
|

Effort–reward imbalance in the school setting: Associations with somatic pain and self-rated health

Abstract: Students are more likely to experience stress-related ill-health when they perceive an imbalance between their effort and rewards. In addition, high overcommitment is associated with an increased risk of ill-health among students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…While most research in this area has focused on service type occupations, and professions with a high degree of human interaction (Tsutsumi & Kawakami, 2004), our research suggests that the ERI model is equally applicable to the study experience, which, for many people, is largely a solitary one (Baik, Sophia, & Naylor, 2015). The model has previously been expanded beyond the workplace to include the education setting, with some literature exploring the health implications of ERI in high schools (Guo et al., 2014; Låftman et al., 2015; Lee et al., 2012). However, our findings provide further justification for the generalization of the ERI model, beyond workplace and compulsory school settings, to university education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While most research in this area has focused on service type occupations, and professions with a high degree of human interaction (Tsutsumi & Kawakami, 2004), our research suggests that the ERI model is equally applicable to the study experience, which, for many people, is largely a solitary one (Baik, Sophia, & Naylor, 2015). The model has previously been expanded beyond the workplace to include the education setting, with some literature exploring the health implications of ERI in high schools (Guo et al., 2014; Låftman et al., 2015; Lee et al., 2012). However, our findings provide further justification for the generalization of the ERI model, beyond workplace and compulsory school settings, to university education.…”
Section: Discussionmentioning
confidence: 99%
“…Despite similarities between the workplace and the university setting, there has not as yet been a great deal of research undertaken to explore the overcommitment hypotheses within the higher education setting. Studies looking at the school setting attempted to assess the overcommitment hypotheses and yet found no support (Låftman et al., 2015). Li et al.…”
Section: Introductionmentioning
confidence: 99%
“…Regression analyses of the sub-dimensions (Table 8) showed that OC was positively associated with emotional exhaustion, but it was negatively associated with inefficacy. From previous findings in academic settings (Fukuda et al, 2010;Laftman et al, 2014), it can be concluded that student OC has different impacts on general health, depending on characteristics of the student population, such as gender and level of schooling. As for engagement, our results are consistent with previous results based on workplace settings (Kinnunen et al, 2008;Wang et al, 2017).…”
Section: Discussionmentioning
confidence: 93%
“…Our fifth hypothesis was that OC would be positively related to the burnout of medical students. Although the relationship between OC and burnout has not been verified in academic settings, it was reported that middle school student OC was associated with somatic pain and poor health (Laftman, Modin, Ostberg, Hoven, & Plenty, 2014). In a sample of medical students, OC was positively correlated with trait anxiety (Hahn et al, 2017).…”
Section: Eri and Burnoutmentioning
confidence: 99%
“…Much of the research focuses on adult health, however, studies from several countries suggest that the decline in health and wellbeing is most apparent among adolescents and young adults. Adolescent girls and young women appear to be at greater risk of poor health and wellbeing than boys and young men [ 3 5 ], with studies showing that physical symptoms (e.g. headaches, tiredness) and emotional distress are increasing [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%